Association of Track & Field Statisticians
Homepage of the A.T.F.S., a world-wide voluntary organisation of enthusiasts devoted to the collection and dissemination of statistics in Track & Field Athletics. Founded in August 1950, we have produced each year since 1951 the authoritative compilation of international athletics statistics, knowngenerally as the "A.T.F.S. Annual" or the "International Athletics Annual".